Wireless Sensor Networks - Tarannum, Suraiya (IntechOpen, 2011)
The importance and ubiquity of wireless networks in the modern age justifies the depth and scope of the chapters included in this book, with its special focus on sensors. Topics covered include MAC protocols, with one contribution offering a literature review on them. Energy efficiency is also important, with several chapters addressing cooperative beamforming, modern spatial-diversity techniques and MEMS. Hardware issues are addressed by a batch of chapters, on extending network coverage areas, CMOS RF transceivers, the use of an accelerometer sensor module and a fall-detection monitoring system and a couple of contributions on hierarchical paradigms in wireless sensor networks. More mathematical approaches are also included, with chapters on data aggregation tree construction and distributed localization algorithms.